Time for truth - "Bunick, Nick" (New Delhi, 2011)
This book is your pathway to a wonderful and joyous new beginning! Nick Bunick fought his way up from the poor city streets to living the American Dream. Then astounding spiritual events occurred in his life that convinced him and hundreds of thousands of others that he had in fact lived 2,000 years ago as the Apostle Paul. His story was featured in the best-selling 1997 book The Messengers, and has dramatically changed the lives of people all over the world. Time for Truth will take you on an incredible journey. It presents you with the true story of what happened 2,000 years ago in the time of Jesus, revealing how messages of love were distorted into messages of fear . . . messages of compassion into messages of guilt. Nick explains how the teachings that were designed to bring us together as brothers and sisters were altered to control the lives of the Christian church$1 (Bs followers and polarize people, leading to centuries of suffering, violence, and war. Nick has committed himself to sharing these extraordinary truths with you, which will have a truly transformative impact on your life. Along the way, you will be given a new and profound understanding of your true relationship with God, the spiritual world, and the purpose of your life.s
Keywords: Spirituality